2013
DOI: 10.1007/s13277-013-1081-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between vestibular schwannomas and mobile phone use

Abstract: Vestibular schwannomas (VSs) grow in the region where the energy from mobile phone use is absorbed. We examined the associations of VSs with mobile phone use. This study included 119 patients who had undergone surgical tumor removal. We used two approaches in this investigation. First, a case–control study for the association of mobile phone use and incidence of VSs was conducted. Both cases and controls were investigated with questions based on INTERPHONE guidelines. Amount of mobile phone use according to du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…In the past decade, mobile phone use has become increasingly common in daily life. Mobile phone helps people maintain social network, but its excessive use is associated with negative health issues, such as mobile phone addiction (MPA) and related somatic and psychological problems …”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, mobile phone use has become increasingly common in daily life. Mobile phone helps people maintain social network, but its excessive use is associated with negative health issues, such as mobile phone addiction (MPA) and related somatic and psychological problems …”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest are studies from Sweden and Korea. In the Korean study, significant increases for acoustic neuroma occurred with >2,000 cumulative hours of use when compared to less (7), and in the Swedish study for >2,300 h of cumulative use (8). In three studies, increased risks for meningioma were also found at the highest cumulative hours of use (5,6,9).…”
Section: Introductionmentioning
confidence: 85%
“…for studies with greater years of use, acoustic neuroma tumor volume increased compared to less years of use (7,12 (6). Potential confounders considered were the level of education, smoking, alcohol consumption, and occupational exposures to pesticides, extremely low frequency electromagnetic fields (ELF-EMF), radiofrequency electromagnetic fields (RF-EMFs), and ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The INTERPHONE study suggested that using cell phones for more than l0 years increases the risk of glioma (Hours et al, 2007) and acoustic tumors (Interphone Study Group, 2011) on the same side of the head as used for cell phones (Interphone Study Group, 2010). A recent human study suggested that vestibular schwannoma tended to occur in the ear used more frequently for a mobile phone and found a strong correlation between tumor volume and the amount of mobile phone use (Moon et al, 2014). Therefore, mobile phones users should be concerned about the potential harmful effects of exposing the brain to RF-EMF.…”
Section: Introductionmentioning
confidence: 99%